Evaluation of endoscopic examination and paranasal computed tomography findings in failed dacryocystorhinostomy patients - Güven Şakalar, Emine; Başmak, Hikmet; Gürsoy, Hüseyin; Çaklı, Hamdi (ENT Updates, 2017)
Objective: The aim of this study is to evaluate endoscopic and paranasal computed tomography (PNCT) findings in cases of failed dacryocystorhinostomy (DCR). Methods: This study included 30 cases of failed DCR (18 females, 12 males; mean age: 49.9±18.9 years) and 30 successful DCR patients (20 females, 9 males; mean age: 56.3±15.9 years). The reasons for the recurrence of the disease were evaluated using preoperative endoscopic examination and PNCT findings. Results: Endoscopic pathology was identified in 24 out of 30 failed cases (80%), while endoscopic pathology was identified in 12 out of 30 successful cases (40%) (p<0.05). PNCT revealed nasal pathology in 24 out of 30 failed cases (80%), and in 15 out of 30 successful cases (50%) (p<0.05). Conclusion: Endonasal and sinonasal pathologies may be associated with DCR failure. Before the commencement of revision DCR, endoscopic examination and PNCT may provide valuable information regarding the underlying etiology.